2021
DOI: 10.18632/aging.202814
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood environment, social cohesion, and epigenetic aging

Abstract: Living in adverse neighborhood environments has been linked to risk of aging-related diseases and mortality; however, the biological mechanisms explaining this observation remain poorly understood. DNA methylation (DNAm), a proposed mechanism and biomarker of biological aging responsive to environmental stressors, offers promising insight into potential molecular pathways. We examined associations between three neighborhood social environment measures (poverty, quality, and social cohesion) and three epigeneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…Two separate studies found that positive aspects of the social environment modified the effects of neighborhood stressors on accelerated DNAm aging. Martin et al ( 81 ) found associations between poor neighborhood quality and accelerated DNAm age; however, associations were only observed among participants living in neighborhoods with low social cohesion. WardCaviness et al ( 132 ) found that poor neighborhood quality was associated with an increased epigenetic mortality risk score (eMRS).…”
Section: Neighborhood Social Environment and Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two separate studies found that positive aspects of the social environment modified the effects of neighborhood stressors on accelerated DNAm aging. Martin et al ( 81 ) found associations between poor neighborhood quality and accelerated DNAm age; however, associations were only observed among participants living in neighborhoods with low social cohesion. WardCaviness et al ( 132 ) found that poor neighborhood quality was associated with an increased epigenetic mortality risk score (eMRS).…”
Section: Neighborhood Social Environment and Dna Methylationmentioning
confidence: 99%
“…Rather than adopting a candidate gene approach, however, the majority of the literature investigates the effect of neighborhood stressors on epigenetic aging. Multiple studies observed accelerated DNAm aging in relation to adverse neighborhood social environment ( 72 , 74 , 81 , 132 ). Two separate studies found that positive aspects of the social environment modified the effects of neighborhood stressors on accelerated DNAm aging.…”
Section: Neighborhood Social Environment and Dna Methylationmentioning
confidence: 99%
“…Dr. Cynthia Rider is a Toxicologist at the National Institute of Environmental Health Sciences and a leading expert in the chemical safety and risk assessment of chemical mixtures ( Catlin et al, 2018 ; Ryan et al, 2019 ; Rider et al, 2021 ). Dr. Cavin Ward-Caviness is a Computational Biologist and Principal Investigator at the U.S. EPA, and he leads studies integrating geospatial exposure measures with molecular biomarkers and health outcome data to understand the impacts of chemical pollutants and social determinants of health ( Ward-Caviness et al, 2020 ; Martin et al, 2021 ; Ward-Caviness et al, 2021 ). Dr. David Reif is a Professor in the Department of Biological Sciences at North Carolina State University (NCSU) and Director of the NCSU Bioinformatics Consulting and Services Core.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of neighborhood as a component of environmental factors has been associated with shortening of telomeres ( Park et al, 2015 ; Gebreab et al, 2016 ; Alexeeff et al, 2019 ). Neighborhood factors have also been associated with epigenetic predictors of all-cause mortality ( Ward-Caviness et al, 2020a ) and with accelerated epigenetic age ( Martin et al, 2021 ). Accelerated epigenetic aging has also been associated with traffic-related air pollution ( Ward-Caviness et al, 2020b ) and fine particulate matter (PM2.5) as well as with organochlorine pesticides ( Lind et al, 2018 ).…”
Section: Biological Susceptibility and Social Vulnerability To Enviro...mentioning
confidence: 99%